BUILDING MAINTENANCE: DETERMINE OF FUNGAL GROWTH ON OFFICE BUILDING USING GEOGRAPHIC INFORMATION SYSTEM (GIS) - Suriani Ngah Abdul Wahab; Munirah Radin Mokhtar; Irwan Mohammad Ali; Md Yusof Hamid, (INTERNATIONAL JOURNAL OF INNOVATION AND INDUSTRIAL REVOLUTION (IJIREV), 2024)
This paper presents the preliminary concept using a Geographic Information System (GIS) to determine fungal growth in an office building, especially in the UiTM Perak branch. As we all know, various viruses and bacteria exist in our environment. The quality of the air affects our health throughout the day. If the quality of the air is polluted, then it is very likely that we will get sick and vice versa. In this research the methodology applied is using geocoding in GIS applications. Analysis using a GIS is used to find the contributing factors to the reproduction of fungi on the walls of the buildings being studied. Based on the obtained results it can be concluded that the proposed methodology creates a convenient, efficient, and inexpensive tool for massive inspection of building resources in large areas. There are several processes to investigate the effects of buildings factors contributing to fungal growth cases such as the creation of rooms database, temperature derivation process and lastly data analysis using the attributes spatial table. Finally, the location of the rooms where the fungal growth is determined is shown by the map results.